THE EFFECT OF GIVING GARLIC PEEL EXTRACT (Allium sativum) THROUGH DRINKING WATER ON THE PERCENTAGE OF CARCASS PARTS OF BROILER AGES 4 WEEKS - I G. A., Pranata; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
This study aimed to determine the effect of garlic peel extract (Allium sativum) through drinking water on the percentage of 4 weeks old broiler carcass parts. The design used in this study was a completely randomized design (CRD) with 4 treatments and 4 replications. Each replication consisted of 5 broilers, so that 80 broilers were used. The treatment of garlic peel extract through drinking water were P0 (Control) without garlic peel extract, P1 (1% garlic peel extract), P2 (2% garlic peel extract) and P3 (3% garlic peel extract). The variables observed in this study included the percentage of carcass, chest percentage, upper thigh percentage, lower thigh percentage, wing percentage, back percentage. The results of the addition of garlic peel extract through drinking water with percentages of content 1%, 2%, 3% and without the addition of extract to the percentage of carcass parts of broilers aged 4 weeks, the results were not significantly different (P>0.05). Based on the results of the study, it can be concluded that the administration of garlic peel extract (Allium sativum) in drinking water of 4 week old broilers did not significantly affect the percentage of carcass parts of 4 week old broilers. Keywords: broiler, garlic skin extract, percentage of carcass part